How close is autophagy-targeting therapy for Alzheimer's disease to clinical use? A summary of autophagy modulators in clinical studies - Fernandes, Sofia Miranda; Mayer, Johanna; Nilsson, Per; Shimozawa, Makoto (Frontiers in Cell and Developmental Biology, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder clinically characterized by progressive decline of memory and cognitive functions, and it is the leading cause of dementia accounting for 60%–80% of dementia patients. A pathological hallmark of AD is the accumulation of aberrant protein/peptide aggregates such as extracellular amyloid plaques containing amyloid-beta peptides and intracellular neurofibrillary tangles composed of hyperphosphorylated tau. These aggregates result from the failure of the proteostasis network, which encompasses protein synthesis, folding, and degradation processes. Autophagy is an intracellular self-digesting system responsible for the degradation of protein aggregates and damaged organelles. Impaired autophagy is observed in most neurodegenerative disorders, indicating the link between autophagy dysfunction and these diseases. A massive accumulation of autophagic vacuoles in neurons in Alzheimer’s brains evidences autophagy impairment in AD. Modulating autophagy has been proposed as a therapeutic strategy for AD because of its potential to clear aggregated proteins. However, autophagy modulation therapy for AD is not yet clinically available. This mini-review aims to summarize clinical studies testing potential autophagy modulators for AD and to evaluate their proximity to clinical use. We accessed clinicaltrials.gov provided by the United States National Institutes of Health to identify completed and ongoing clinical trials. Additionally, we discuss the limitations and challenges of these therapies.